Strategi Pemerintah Daerah dalam Meningkatkan Ketahanan Pangan Daerah (Studi pada Kabupaten Malang) - Fiandana, Yanuar (Jurnal Administrasi Publik, 2015)
Abstract: The strategy of The Local Government in Increasing the Local Food Security (The study was conducted in Malang). The development of food security is the responsibility of the government as well as the local community. The joint of those two agents will help to develop the good food security in providing the food for the entire population, especially the food derived from the local production. Besides that, the good food security is expected to provide the food in sufficient number and variety along with concerning the savety and the affordable issue. In order to create that condition, strategy is needed in increasing the food security itself. Local Government of Malang  together with Badan Ketahanan Pangan Pelaksana dan Penyuluhan (BKP3) has sought to improve regional food security through the development of the community rice barn, accelerating the variety of food and nutrient, forming Dewan Ketahanan Pangan, and applying the Program Desa Mandiri pangan. The result showed that the strategy applied by the local goverment of Malang in increasing the food security has met the demand of the food security aspects.  Keywords: strategic management, food security  Abstrak: Strategi Pemerintah Daerah dalam Meningkatkan Ketahanan Pangan Daerah (Studi pada Kabupaten Malang). Pembangunan ketahanan pangan merupakan tanggung jawab bersama antara pemerintah dengan masyarkat untuk mewujudkan ketahanan pangan dalam menyediakan pangan bagi seluruh penduduk, terutama yang berasal dari produksi dalam negeri, dalam jumlah dan keragaman yang cukup, aman, dan terjangkau. Untuk mewujudkan kondisi tersebut, maka diperlukan suatu strategi dalam meningkatkan ketahanan pangan. Pemerintah Kabupaten Malang melalui Badan Ketahanan Pangan Pelaksana dan Penyuluhan (BKP3) telah berupaya dalam meningkatkan ketahanan pangan daerah melalui pengembangan lumbung pangan, mempercepat penganekaragaman konsumsi pangan dan gizi, mementuk Dewan Ketahanan Pangan, pengembangan desa mandiri pangan. Hasil penelitian menunjukkan bahwa strategi yang dijalankan oleh pemerintah Kabupaten Malang dalam meningkatkan ketahanan pangan daerah sesuai aspek-aspek ketahanan pangan.   Kata kunci: manajemen strategi, ketahanan pangan